Critical Analysis of Service Quality Concerning Local and International Financial Institutions in Malaysia - Yeow, Hoe Cheng (2003)
This study attempts to measure and compare the level of service quality offered by international and local financial institutions in Malaysia. This research was conducted to investigate whether it is true that international banks do provide a higher level of service quality compared to local banks from the perceptions and expectations of their respective customers. This study will also offer the opportunity to observe reasons as to why local banks are unable to provide a competitive level of service quality as well as determine what criteria or factors banking consumers hold more important than others. Two financial institutions will be chosen for the purpose of this study, one from existing ten local banks and one from the group of international banks. Data collection will be carried out by way of a survey on the customers having facilities with these two banks. Subsequently, the GAP model and SERVQUAL instrument will be used as the framework for the basis of the study and as the measuring tool in the survey. Perceived service quality will be measured on a 25 item Likert scale using a nondifference approach to obtain the gap data. Correlation analysis of the data will then be carried out to achieve the objectives of this study. The results of this study complies with the claims that international banks do indeed provide a higher level of service relative to local banks. From the analysis we also managed to highlight the factors where customers place similar importance on and factors where both groups of customers differ on the level of importance. Reasons as to why the level of service quality differs as well as the difference in importance placed on the items used are brought up in the discussions section. To conclude, a summary of the study together with its limitations is presented as well as suggestion for further study.